Application of a 3R-method: Time-dependent spasmolytic effect of nonylphenols (NPs) and nonylphenolethoxylates (NPEs) - Maria Fuerhacker; Christian R Studenik (Open Journal of Environmental Biology - Peertechz Publications, 2022)
Nonylphenol ethoxylates (NPEs) are non-anionic surfactants that were used as detergents, emulsifiers, wetting, and dispersing agents in a wide variety of consumer products, commercial products, and many industrial cleaning processes. In some parts of the world such as China or South Africa, nonylphenol (NP) and NPE remain a problem. NP and short-chained NPE as breakdown products are toxic and considered endocrine disruptors. This study used a 3R-method to investigate the time-dependent spasmolytic effect in isolated terminal ilea of guinea pigs. Nonylphenol (4-NP), nonylphenol-n-ethoxylate (NP3) and 4-n-nonylphenol (4-n-NP) with a straight nonyl-chain were used. 4-n-NP did not show a significant time-dependent effect, whereas NP3 resulted in a time-dependent decrease in the force of contraction. 4-NP in a concentration of 3 µmol/l caused a decrease and a concentration of 10 µmol/l initially increased and then decreased the force of contraction. The inference from this study is that the branching of the NP and the ethoxylates had different spasmolytic effects and the results indicate that this organ model could supplement in-vitro 3R test batteries to screen for environmental effects.